Analysis and improvement of route switch in IEEE 802.11s - Bo YOU; Yue-peng YAN (Tongxin xuebao)
Analyzed the route switch of hybrid wireless mesh protocol(HWMP)in IEEE 802.11s and made an improve-ment to reduce the packet lost rate when routes switching was analyzed.Based on the received signal strength indica-tor(RSSI)a scheme with judgment threshold in mesh peer link management protocol was proposed,which controlled the status of peer link to change the timing of route switch.In this way,the packet lost was avoided.The experimental results show that the improvement reduces the packet lost rate by 2%~5% compared with traditional IEEE 802.11s in uncon-trolled wireless environment when nodes moving in low speed.